Atividade antimicrobiana de porfirina catiônica 4-H2TMeP frente a bactérias multirresistentes cultivadas em biofilmes e sobre fragmentos de pele de cães - Bernicker, Mayara Rosa (2024)
Canine integumentary infections caused by antimicrobial-resistant microorganisms constitute a One Health threat. This is attributed to the potential transmission from animals to their owners, becoming particularly alarming when these microorganisms demonstrate resistance to more than three classes of antimicrobials, characterizing them as multidrug-resistant (MDR). These infections may arise from multiple microorganisms that frequently organize into biofilms. Biofilm formation not only contributes to infection persistence but also poses an additional challenge to treatment, as bacteria within these communities exhibit increased resistance to conventional antimicrobial. Therefore, considering the multidrug resistance and the bacteria's ability to colonize skin surfaces in biofilm, an urgent search for alternative methods of microbial inactivation is imperative. Antimicrobial Photodynamic Therapy (aPDT) using porphyrins has shown promise in inactivating viruses, yeasts, and bacteria. Numerous in vitro studies demonstrate that the tetra-cationic porphyrin 4-H2TMeP can effectively inactivate bacteria, possessing the advantage of easy commercial availability, water solubility, and multi-target action through singlet oxygen production. Thus, this dissertation aimed to evaluate the antibacterial activity of the porphyrin 4-H2TMeP against mono-and polymicrobial biofilms cultivated by MDR bacteria and on canine skin fragments. The porphyrin 4-H2TMeP was tested against three clinical MDR isolates of Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus pseudintermedius. In all experiments, a non-cytotoxic concentration of 40 µM 4-H2TMeP was used. Biofilms in monoculture and mixed cultures (S. pseudintermedius + E. coli) were treated with 4-H2TMeP and exposed to white LED light irradiation for 30, 60, and 90 minutes. In canine skin fragments, monocultures were treated with 4-H2TMeP and irradiated for 30 (S. pseudintermedius), 60 (E. coli), or 60 and 90 minutes (P. aeruginosa); polymicrobial cultures containing S. pseudintermedius and E. coli were subjected to irradiation for 60 and 90 minutes. The effectiveness of aPDT was evaluated by counting colony-forming units (CFUs) from biofilm and swabs collected from skin fragments containing bacterial cultures, which were then cultured in media post-treatment. The seeded plates were incubated for 24 hours at 37 °C in aerobic conditions, and statistically compared CFUs were assessed between treated and control groups. Results demonstrated that 4-H2TMeP reduced concentrations of S. pseudintermedius and E. coli in individual and mixed biofilms, significantly decreasing bacterial concentrations (p < 0.05) in mono- and polymicrobial cultures grown on canine skin samples, with emphasis on S. pseudintermedius inactivation. However, no significant reduction in P. aeruginosa was observed in consolidated biofilms and monocultures on dog skin, even with extended irradiation time. The results obtained in this study are promising and encourage further in vivo experiments using the 4-H2TMeP porphyrin in aPDT to inactivate MDR bacteria in animal skin lesions, potentially validating its clinical use in cases unresponsive to conventional therapy